(untitled) (Analele Universității București. Limba și literatură română, 2024)
This article examines Differential (Direct) Object (DOM) and Agent Marking (DAM) in (contemporary) Romanian on the basis of written data coming mostly from the internet. It shows that both phenomena are optional (with some exceptions for certain types of Direct Objects) and that they are both triggered by the parameter of animacy which is a necessary one. While DOM may additionally be triggered by specificity and topicality, DAM is not sensitive to specificity and it may be affected by language register (namely the official / administrative register).